The shape memory effect in melt spun Fe-15Mn-5Si-9Cr-5Ni alloys - Druker, Ana Velia (2013)
At room temperature, Fe-15Mn-5Si-9Cr-5Ni alloys are usually austenitic and the application of a stress induces a reversible martensitic transformation leading to a shape memory effect (SME). However, when a ribbon of this material is obtained by melt-spinning, the rapid solidification stabilizes a high-temperature ferritic phase. The goals of this work were to find the appropriate heat treatment in order to recover the equilibrium austenitic phase, characterize the ribbon form of this material and evaluate its shape memory behaviour. We found that annealing at 1050ºC for 60 min, under a protective argon atmosphere, followed by a water quenching stabilizes the austenite to room temperature. The yield stress, measured by tensile tests, is 250 MPa. Shapememory tests show that a strain recovery of 55% can be obtained, which is enough for certain applications.